EPIDEMIOLOGY OF SEASONAL INFLUENZA OUTBREAK AMONG IRAQI POPULATION:2018 - & et al., Aufi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study aimed to highlight the prevalence of the seasonal influenza in the different Iraqi provinces during 2018 year to study the epidemiological aspects, and their effect on the frequency of disease and death cases caused by influenza virus. A total of 1359 throat and nasal swabs was collected from individuals suffering from influenza like illness (ILI) or severe acute respiratory infection (SARI) for testing influenza virus type A (H1N1 and H3N2) and type B. RNA extracted and amplification with specific primers and probes. Results showed the incidence rate of flu A 16.7 (227/1359) and 4.7 of flu B per 100000 people-year that included 14.9 for H1N1, 1.5 for H3N2 and the remaining value for mixed infection of H1N1 and H3N2. Regarding, the mortality rate 1.6 (21/227) with influenza A and 0.15 (2/64) with influenza B infections per 100000 person-year. The prevalence of flu A between the months showed significant differences, especially in the first two months of the year. The distribution of influenza infections in Baghdad province, which appeared the highest peak, then followed by Babyl, Waist and Salahaddin provinces. In conclusion, more surveillance studies are needed each year to provide database more important for WHO Eastern Mediterranean region (EMR) of influenza surveillance.